Behavior of Leaf Meristems and Their Modification - Ichihashi, Yasunori; Tsukaya, Hirokazu (Frontiers in Plant Science, 2015)
A major source of diversity in flowering plant form is the extensive variability of leaf shape and size. Leaf formation is initiated by recruitment of a handful of cells flanking the shoot apical meristem to develop into a complex three-dimensional structure. Leaf organogenesis depends on activities of several distinct meristems that are established and spatiotemporally differentiated after the initiation of leaf primordia. Here, we review recent findings in the gene regulatory networks that orchestrate leaf meristem activities in a model plant Arabidopsis thaliana. We then discuss recent key studies investigating the natural variation in leaf morphology to understand how the gene regulatory networks modulate leaf meristems to yield a substantial diversity of leaf forms during the course of evolution.